Model Kematian Jalan Raya di Malaysia: Unjuran Tahun 2000 - Radin Sohadi, Radin Umar (Universiti Putra Malaysia Press, 1998)
Traffic accidents are one of the main causes of deaths in Malaysia. To address this problem, a Cabinet Committee on Traffic Safety was established by the Prime Minister and a target of reducing fatalities by 30% by the year 2000 was set up. This paper presents a more realistic approach on determining the above set objective. A fatality model based on time series log-linear model was established to explain the relationship between traffic deaths and traffic exposures, namely population, vehicles and road length. The effect of the change in recoding system was also included in this analysis.